2011
DOI: 10.1186/1750-0680-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of carbon in woody plants and soil across a vineyard-woodland landscape

Abstract: BackgroundQuantification of ecosystem services, such as carbon (C) storage, can demonstrate the benefits of managing for both production and habitat conservation in agricultural landscapes. In this study, we evaluated C stocks and woody plant diversity across vineyard blocks and adjoining woodland ecosystems (wildlands) for an organic vineyard in northern California. Carbon was measured in soil from 44 one m deep pits, and in aboveground woody biomass from 93 vegetation plots. These data were combined with phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 76 publications
0
31
1
1
Order By: Relevance
“…Salomé et al (2016) found similar results for carbon content under permanent plant cover. Williams et al (2011) showed that scaling up vine management to landscape level, by maintaining wildlands in mosaic organization with vineyards, could be beneficial for increasing overall C stocks. As for carbon balance, it is important to take into account the global carbon footprint of vineyard cropping systems as mechanized soil tillage and service crop mowing can increase CO2 production from fossil fuels.…”
Section: Carbon Sequestration and Mitigation Of Climate Changementioning
confidence: 99%
“…Salomé et al (2016) found similar results for carbon content under permanent plant cover. Williams et al (2011) showed that scaling up vine management to landscape level, by maintaining wildlands in mosaic organization with vineyards, could be beneficial for increasing overall C stocks. As for carbon balance, it is important to take into account the global carbon footprint of vineyard cropping systems as mechanized soil tillage and service crop mowing can increase CO2 production from fossil fuels.…”
Section: Carbon Sequestration and Mitigation Of Climate Changementioning
confidence: 99%
“…Agricultural landscapes that include perennial woody crops, such as vineyards, represent a major source of potential C storage or release (Williams et al, 2011). Almagro et al (2009) showed, under Mediterranean conditions, different soil CO 2 effluxes between land uses and, within uses, between beneath-and intercanopy sites.…”
Section: Introductionmentioning
confidence: 99%
“…The results presented prove that a higher level of land management and farm stewardship could lead to the maximization of carbon stocks in vineyard landscapes, by implementing legislative actions to avoid the conversion of forest lands with high potential of carbon storage (Jackson et al, 2003). For instance, a study conducted by Williams et al (2011) showed that even old vines with high aboveground carbon content were only capable of retaining 25% of carbon as compared to surrounding wooded areas.…”
Section: 4mentioning
confidence: 76%
“…In addition, LUCs have allowed GHG emissions in Spain to be substantially lower in the past decades due to afforestation of many agricultural lands that were abandoned due to enforcements from the European Union's Common Agricultural Policy. However, viticulture has shown in previous studies to be a potential threat to the loss of natural habitat and species diversity, as well as a net emission of carbon to the atmosphere (Carlisle et al, 2006;Underwood et al, 2009;Williams et al, 2011). Therefore, the repeated exclusion of carbon storage and emissions due to LUCs, woody biomass in the vineyards and soil management from LCA studies may provoke an underestimation of the GHG emissions that are occurring in vineyard landscapes.…”
Section: Introductionmentioning
confidence: 88%